Differential diagnosis of changes in the area of the large duodenal nipple in postcholecystectomy syndrome by the method of parietal impedancemetry - Veligotsky, N. N.; Aleksanian, К. А.; Arutyunov, S. E.; Shadrin, O. V. (Modern medical technology, 2021)
Purpose of the study. To carry out differential diagnostics of organic and functional changes in the area of the large duodenal papilla (LDP) by the method of parietal impedancemetry in patients with PCES. Materials and methods. Duodenoscopy with parietal impedance LDP was performed in 47 patients. A history of 38 patients underwent laparoscopic cholecystectomy, and 9 patients underwent laparotomic cholecystectomy. In 31 patients, the study was performed against the background of signs of obstructive jaundice, in 16 – the study was performed against the background of dilatation of the common bile duct without visualization of calculi in it. All patients underwent endoscopic retrograde cholangiopancreatography with determination of parietal impedance prior to endoscopic papillosphincterotomy. The control group consisted of 8 patients without manifestations of PCES, who underwent duodenoscopy with parietal impedancemetry during a routine examination. Results. The parameters of the parietal impedance of patients with PCES against the background of benign obstructive jaundice in the presence of papillitis were 605–703 Ohm. In the absence of visual signs of inflammation, the resistance of the LDP wall varied within 760–820 Ohm and coincided with the values of the control group. Conclusion. Parietal impedancemetry is an informative method for detecting inflammatory changes in the LDP, which can be performed routinely during duodenoscopy and allows differential diagnosis between the organic pathology of the LDP zone and its absence.